Epilepsy surgery of the rolandic and immediate perirolandic cortex: Surgical outcome and prognostic factors. Issue 10 (8th August 2014) - Delev, Daniel; Send, Knut; Wagner, Jan; von Lehe, Marec; Ormond, D. Ryan; Schramm, Johannes; Grote, Alexander
Summary Objective Herein we present a single‐center retrospective study of patients who underwent epilepsy surgery for seizures arising from the sensorimotor (rolandic) cortex. The goal was to find prognostic factors associated with better seizure outcome and to evaluate both surgical and neurologic outcomes. Patients, methods, and materials A total of 66 patients fulfilled eligibility criteria and were included in the study. Patients were divided into two groups for analysis: patients with resections within rolandic cortex (RO group; n = 46), and patients with resections in immediate perirolandic cortex and simultaneous sensorimotor multiple subpial transections (IPR group; n = 20). Results Favorable postoperative seizure outcome (International League Against Epilepsy [ILAE]; ILAE1–ILAE3) was achieved in 42 patients (64%), 39 (59%) of whom were completely seizure‐free (ILAE1). The favorable seizure outcome in the RO group (72%) was better than in the IPR group (45%) (p = 0.04, relative risk [RR] 0.51 [0.28‐0.94, 95% CI]). Eighteen patients (34%) had a postoperative permanent neurologic deficit. Independent predictors for excellent seizure outcome (ILAE1) after multivariate regression analysis were complete resection of the lesion (p < 0.001), pathology (p = 0.009), age at surgery (p = 0.03), and the absence of preoperative simple partial seizures (p = 0.01). Significance With a 64% favorable seizure outcome, surgery for intractable epilepsy arising from sensorimotor cortex is possible and can be worthwhile. The increased risk for postoperative neurologic deficits is higher than in other locations, and this must be discussed with patients in detail prior to surgery. Best postoperative results can be achieved in cases in which a complete resection is possible without damaging eloquent cortical areas.